Diversidade e infectividade de assembléias de anofelinos em cinco localidades ao longo do Rio Oiapoque, na área de fronteira com a Guiana Francesa, Oiapoque, Amapá - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
Malaria is a major public health problems in Brazil and abroad, widely distributed in tropical and subtropical regions. In 2013, there were 198 million cases of malaria, 584 thousand deaths around the world, affecting mainly in Africa. In 2014, Brazil have been reported 142,941 cases of malaria, 119,090 positive for Plasmodium vivax, Plasmodium falciparum to 22,104, 27 to Plasmodium malariae and 1055 to mixed cases of malaria (Plasmodium falciparum and Plasmodium vivax). In the last five years Oiapoque municipality had a significant decrease in autochthonous cases of malaria in 2009 were 3,387 and in 2014 was record-933, there was a reduction of 72.5%. This study aimed to evaluate the composition and infectivity of Anopheles assemblies in five locations along the River Oiapoque, on the border area with French Guiana, Oiapoque, Amapá. Five locations were studied in the city of Oiapoque: Bairro Paraíso, Vila Vitória, Vila de Santo Antônio, Ilha Bela e Vila Brasil. In October and November 2013 and April 2014. Were collected and identified adult and immature Anopheles, assessing the density by location, infectivity rate, and parity rate. In five locations have been identified 1315 specimens of Anopheles, with 1282 Anopheles darlingi (97.5%), 14 Anopheles nuneztovari (1.6%), 14 Anopheles triannulatus (1.06%) and 5 Anopheles braziliensis (0,38%), as follows: Bairro Paraíso 911 (69.3%), Vila Vitória 235 (17.9%), Vila Santo Antônio 104 (7.9%), Ilha Bela 65 (4.9%) and Vila Brasil (0%). The infectivity rate of the species was 1.44% (2/138) for Plasmodium falciparum and Plasmodium vivax to 0.72% (1/138) in Bairro Paraíso and 1.81% (1/55) for Plasmodium falciparum and 1.81 (1/55) for Plasmodium vivax in Ilha Bela. The parity rate in the studied areas was over 60% in intradomiciliary in Bairro Paraíso and Vila Vitória, demonstrating the possibility of malaria transmission in the home environment. Low diversity of Anopheles at collection points was found, with only four recorded species: Anopheles darlingi, Anopheles nuneztovari, Anopheles triannulatus and Anopheles braziliensis. With a predominance of Anopheles darlingi species representing 97.5% of the captured specimens. Bairro Paraíso had higher vector density compared to other surveyed locations. The high density of vectors added to the malaria cases in the municipality of Oiapoque contributes to the dynamics of disease transmission on the border between Brazil and French Guiana
Keywords: Malária - Aspectos sociais - Oiapoque (AP); Plasmodium; Parasitologia; CNPQ::CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA; CNPQ::CIENCIAS BIOLOGICAS::PARASITOLOGIA::ENTOMOLOGIA E MALACOLOGIA DE PARASITOS E VETORES; VALIDAÇÃO BIOLÓGICA DE PRODUTOS NATURAIS E SINTÉTICOS; ENSAIOS BIOLÓGICOS